2012
DOI: 10.1097/iop.0b013e318220863f
|View full text |Cite
|
Sign up to set email alerts
|

Dacryocystorhinostomy Precipitating Keratoconjunctivitis Sicca in Aplasia of Lacrimal and Major Salivary Glands (ALSG)

Abstract: We report a 16-month-old girl referred for bilateral epiphora and sticky eyes since birth. Examination revealed a refluxible left lacrimal sac mucocele, agenesis of the left lower punctum, and agenesis of both puncta on the right side. Complete bony obstruction was noted on probing of the left nasolacrimal duct. At 4 years of age, she underwent left external dacryocystorhinostomy (DCR) with silicone intubation because of chronic dacryocystitis. Her epiphora and stickiness improved significantly in the first po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Should dacryocystitis occur, after resolution of infection with medical treatment, there are several alternatives to standard DCR. These include careful observation with early antibiotic treatment in case of re-infection, DCR surgery with secondary punctal plug placement, 15 prosthetic replacement of the ocular surface ecosystem lens use, or dacryocystectomy. A multidisciplinary team experienced in the diagnosis and treatment of GVHD is necessary for optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Should dacryocystitis occur, after resolution of infection with medical treatment, there are several alternatives to standard DCR. These include careful observation with early antibiotic treatment in case of re-infection, DCR surgery with secondary punctal plug placement, 15 prosthetic replacement of the ocular surface ecosystem lens use, or dacryocystectomy. A multidisciplinary team experienced in the diagnosis and treatment of GVHD is necessary for optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of lacrimal glands it’s related with irritable eyes symptoms, infections and even epiphora if the duct or puncta is involved (1). Nevertheless, the patients with ASLG syndrome usually don’t present any symptoms because the tear secretion is reduced but at the same time, balanced by the diminished drainage caused by alteration of the duct and/or puncta (17). This fact can be confirmed by a Schirimer test (12).…”
Section: Discussionmentioning
confidence: 99%
“…Also it is suggested that in ASLG the symptoms are presented earlier (1). Serum test must be realized to reject a systemic syndrome (1,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations